2022
DOI: 10.3390/cancers15010273
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Telomerase Activity in Subcutaneous and Visceral Adipose Tissues from Obese and Non-Obese Patients with and without Colorectal Cancer

Abstract: To investigate the molecular mechanisms that link obesity and colorectal cancer (CRC), we analyzed parameters related to telomere function in subcutaneous and visceral adipose tissues (SAT and VAT), including subjects with and without CRC, who were classified according to their body mass index (BMI). Adipose tissues were obtained from 147 patients who had undergone surgery. A total of 66 cases corresponded to CRC patients, and 81 subjects were not affected by cancer. Relative telomere length was established by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Among the cellular factors that correlate with aging, one of the most remarkable is TL. Thus, TL has been established as a useful and easily measurable marker by RT-qPCR [ 9 , 10 , 11 , 12 ], although there are other approaches for its quantification, such as terminal restriction fragment (TRF) length measurement by Southern blot [ 13 , 14 ]. In this regard, a study on germline telomere shortening by Lisa Boardman et al showed that longer telomeres increased the risk of developing EOCRC, whereas shorter telomeres were associated with late-onset CRC [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the cellular factors that correlate with aging, one of the most remarkable is TL. Thus, TL has been established as a useful and easily measurable marker by RT-qPCR [ 9 , 10 , 11 , 12 ], although there are other approaches for its quantification, such as terminal restriction fragment (TRF) length measurement by Southern blot [ 13 , 14 ]. In this regard, a study on germline telomere shortening by Lisa Boardman et al showed that longer telomeres increased the risk of developing EOCRC, whereas shorter telomeres were associated with late-onset CRC [ 15 ].…”
Section: Discussionmentioning
confidence: 99%